The Design of Digital Heart Rate Meter Using Microcontroller - Padang Tunggal, Tatiya; Asta Juliani, Shela; Agus Widodo, Hendro; Andri Atmoko, Rachmad; Thanh Nguyen, Phong (Journal of Robotics and Control (JRC), 2020)
Cardiac tests generally use an electrocardiograph, the results of which are used by medical teams to diagnose heart conditions. Individual ECG examination is held in a health care institution so that it cannot be held independently, considering the high costs and the need for analysis by a specialist.Â  It is, therefore, necessary to have a functional and portable device to detect heart rate. The heart rate measuring device, equipped with a finger sensor, was designed for adults. The 15-second measurement interval showed the heart rate in one minute and the results were shown on an LCD. The minimum system circuit used ATMega 16.